Reporte De Caso Clínico De Linfoma Canino Multicéntrico, Durante El Desarrollo De Pasantía En El Centro Oncológico Veterinario, Bogotá (2023)
The present work was carried out with the purpose of describing the activities carried out during the internship at the Veterinary Oncology Center, which include medical consultation (assistance), sample taking, support in chemotherapy procedures, rotation in abdominal ultrasound, assistance in interconsultation and assistance in oncological surgical procedures and in turn present a clinical case of grade I multicentric canine lymphoma that was diagnosed and classified thanks to the physical examination, hematological, imaging and cytological studies.